Design and fabrication of ceiling fan blades cleaner - Mohd Faizal, Jasni (2008)
This thesis is based on the project about design and fabrication of ceiling fan blades cleaner. 'Ceiling fan blades cleaner' is device that can clean the top and bottom of surface ceiling fan blades. The fabrication of this product started with article review. All information about ceiling fan blades cleaner such as design, price, material that had been used for the product specification analysis, concept designing, detail concept designing and fabrication of the product. From the analysis, a new design of ceiling fan blades cleaner has been created. The investigation was made in scope of the constraint that may occur for the development of the product and relevance of the product manufacturing processes. This product have been fabricate according to fabrication process such as welding, cutting, drilling and assembling. For development of this project and future works, some suggestion was made for upgrading the product. The suggestion like the flexibility on these ceiling fan blades cleaner and more lightweight on the holder will competitive with the existing products in the market.